PENINGKATAN HASIL BELAJAR PESERTA DIDIK MATERI TEKS DEBAT MELALUI PEMBELAJARAN TIME TOKEN DI KELAS X MM 1 SMK NEGERI 1 PUNGGING - IM. SHOFI’I (Discovery, 2023)
The purpose of this research is to know the results of the implementation of the time token learning method based on the implementation of the lesson plans that have been developed, and the activities during student learning and learning outcomes related to debate material. The research being conducted was classroom action research conducted in Class X MM 1 Semester 2 of the 2019/2020 Academic Year at SMK Negeri 1 Pungging involving 32 students. The results of the research that has been carried out explain that the application of the time token learning method is able to provide an increase in student learning outcomes. This is evidenced by the percentage value of student learning test results which was only 16.63% in the initial conditions, then in the first cycle it became 75% and increased to 93.37% in the second cycle. The lesson plan implementation section also experienced an average increase, namely the average score from 2.75 in the first cycle to 3.64 in the second cycle and the lesson plan implementation section received a score of 100% in both cycles. In the student activity section it is also shown that learning is student-centered, this can be seen from the increase in the percentage when implementing time token learning and discussions and there is a decrease in inappropriate/inappropriate behavior.